2009
DOI: 10.1007/s10571-009-9393-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Neuroprotective Effects of Valproic Acid on Primary Motor Neurons in Monoculture or Co-cultures with Astrocytes or Schwann Cells

Abstract: Chronic dysregulation of the intracellular Ca(2+) homeostasis (excitotoxicity) is thought to contribute to the development of motor neuron diseases. Valproic acid (VPA) is widely used as an antiepileptic drug and acts mainly by inhibition of sodium channels and by enhancing the level of the inhibitory neurotransmitter gamma-aminobutyric acid. Neuroprotective capacities of VPA are supposed to arise also from the inhibition of histone deacetylases. We investigated the viability of highly purified rat embryonic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…All treatment described below were performed after 7 days in vitro (DIV 7). The purity of primary motor neuron cultures was determined by the ratio of SMI32 positive cells to DAPI stained nuclei, resulting in approximately 80% motor neurons [46], [47].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All treatment described below were performed after 7 days in vitro (DIV 7). The purity of primary motor neuron cultures was determined by the ratio of SMI32 positive cells to DAPI stained nuclei, resulting in approximately 80% motor neurons [46], [47].…”
Section: Methodsmentioning
confidence: 99%
“…Cell nuclei were stained with 4′, 6-diamidino-2-phenylindole (DAPI; Invitrogen, Darmstadt, Germany). Motor neuron and astrocyte survival was quantified by cell counting in 5 visual fields of each coverslip in a total of eight different preparations for both non-transgenic and transgenic cells, as previously described [46], [47].…”
Section: Methodsmentioning
confidence: 99%
“…Higher concentrations ([100 lM), however, were considerably toxic for primary motoneurons dissected from spinal cords. We had further shown dose dependent neurotoxic effects of the glutamate receptor agonist KA in three different motor neuron culture systems which validate them as a proper tool to study exitotoxicity in vitro and to screen potentially neuroprotective compounds (Ragancokova et al 2009). To overcome the problem of adverse effects of VPA administered in higher dosages, a number of chemical derivates of VPA have been synthesized.…”
Section: Discussionmentioning
confidence: 85%
“…In a previous study we had shown a dose-dependency of the effect of VPA on motoneuron survival and a marginal neuroprotective effect against KA-induced neurotoxicity in presence of glial cells (Ragancokova et al 2009). …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation